2007
DOI: 10.1007/s00253-007-0926-8
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic growth and potential for amino acid production by nitrate respiration in Corynebacterium glutamicum

Abstract: Oxygen limitation is a crucial problem in amino acid fermentation by Corynebacterium glutamicum. Toward this subject, our study was initiated by analysis of the oxygen-requiring properties of C. glutamicum, generally regared as a strict aerobe. This organism formed colonies on agar plates up to relatively low oxygen concentrations (0.5% O2), while no visible colonies were formed in the absence of O2. However, in the presence of nitrate (NO3¯), the organism exhibited limited growth anaerobically with production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 50 publications
(31 reference statements)
2
73
0
Order By: Relevance
“…Complete medium BY [26] was used for cultivation of C. glutamicum. Solid plates were made by the addition of Bacto-Agar (Difco) to 1.6%.…”
Section: Mediamentioning
confidence: 99%
“…Complete medium BY [26] was used for cultivation of C. glutamicum. Solid plates were made by the addition of Bacto-Agar (Difco) to 1.6%.…”
Section: Mediamentioning
confidence: 99%
“…It has been previously reported that nitrate reductase activity was not influenced by the oxygen and nitrate levels, although aerobically growing C. glutamicum cells exhibited no significant nitrite production in the presence of oxygen (Takeno et al, 2007). This may be explained by preferential electron flow to oxygen due to the higher electron-accepting affinity of cytochrome oxidase than nitrate reductase enzymes.…”
Section: Discussionmentioning
confidence: 74%
“…C. glutamicum has long been regarded as an aerobic bacterium because there have been few reports of its growth by anaerobic respiration or fermentation, despite the fact that most other coryneform bacteria are facultative anaerobes (Liebl, 2001). Recently, anaerobic growth of C. glutamicum by nitrate respiration was reported (Nishimura et al, 2007;Takeno et al, 2007). This property is attributed to the presence of a narKGHJI operon.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is taken as a given that the amount of antifungal compound in an agar-plug colony assay (APCA) is proportional to the size of the inhibition zone on the plate [21]. To test the feasibility of the APCA method for CyA-producing T. niveum, several paper discs containing various amounts of CyA were first applied to a lawn of Aspergillus niger cultured on a ME medium (malt extract 20 g, glucose 20 g, peptone 1 g, agar 20 g, in 1 l of distilled water) for 2 days.…”
mentioning
confidence: 99%